2007
DOI: 10.1007/s00402-007-0423-7
|View full text |Cite
|
Sign up to set email alerts
|

Trochanteric fractures in the elderly: the influence of primary hip arthroplasty on 1-year mortality

Abstract: Introduction The aim of the study was to compare the mortality risk and complication rate after operative treatment of pertrochanteric fractures with primary arthroplasty, dynamic hip screw (DHS) or proximal femoral nail (PFN). Patients and methods Clinical records including X-rays of all patients with trochanteric femoral fractures, except pathologic fractures and a minimum age of 60 years, which were treated between 1992 and 2005 were entered in this retrospective study. Of these 283 patients, 132 were treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 34 publications
2
60
0
9
Order By: Relevance
“…Haentjens et al 27 and Geiger et al 28 in their case series showed dislocation rate in the patient group who underwent total hip arthroplasty was significantly higher (12% to 44.5%) than those who had bipolar arthroplasty(0 to 3.3%). We too had two (1.5%) patients who had got dislocated post-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…Haentjens et al 27 and Geiger et al 28 in their case series showed dislocation rate in the patient group who underwent total hip arthroplasty was significantly higher (12% to 44.5%) than those who had bipolar arthroplasty(0 to 3.3%). We too had two (1.5%) patients who had got dislocated post-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…Complications such as excessive sliding (leading to shortening), varus displacement, nail pull-out, and/or screw breakage are some of the problems commonly seen in these osteoporotic patients who had been treated by dynamic hip screw (DHS). 1,2 Although this implant is the standard treatment for unstable intertrochanteric fractures, it is associated with high rate of complications and morbidity, and therefore primary hip arthroplasty was also suggested as an alternative treatment by some authors. [2][3][4] In addition, DHS is not usually recommended in unstable reverse oblique fractures.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Although this implant is the standard treatment for unstable intertrochanteric fractures, it is associated with high rate of complications and morbidity, and therefore primary hip arthroplasty was also suggested as an alternative treatment by some authors. [2][3][4] In addition, DHS is not usually recommended in unstable reverse oblique fractures. 2,5,6 Intramedullary devices like the proximal femoral nail have been reported to have an advantage in such fractures as their placement allowed the implant to lie closer to the mechanical axis of the extremity, thereby decrease the lever arm and bending moment on the implant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chances of fall increase with patient age. [2][3][4] Management options are wide with conservative and surgical management. Conservative management have largely been given up due to significantly poor results.…”
Section: Introductionmentioning
confidence: 99%